Analysis on the harmonic structure of David’s Concertino for trombone / Mohd Mustaqim Abdullah - Abdullah, Mohd Mustaqim (2012)
This is a study of the harmonic structure in the Early Romantic period, focusing on the composition by Ferdinand David entitled Concertino for Trombone Opus 4. This study has been carried out mainly in Universiti Teknologi MARA, Shah Alam. The first chapter of this research is an utter explanation of the study; its background, problem statement, research questions, research objectives, significance of the study, and limitations of the study. From this section, readers will have a clear understanding and overview of the direction and scope of the research. The second chapter is a review of literature that is related to the study. Based on the literature, the researcher recognises several main ideas and concepts of harmony that are related to the study of the concerti no. An overview of the harmonic style of the Early Romantic period includes a discussion on the topics chromaticism and modulations. Under chromaticism, a new concept of functionality will be explained. The third chapter discusses about the method used by the researcher in the process of collecting and analysing data. For this study, only secondary data is collected as no interviews or questionnaires were carried out. As for the analysis of the data, the researcher compares his findings to information and facts learnt from books and publications. Findings and results of the study are laid out in chapter four of this paper. In this section the researcher discusses the information gathered to meet the research objectives. In the final part of the research which is chapter five, readers will be presented with a summary and conclusion of the whole writing and what the researcher has gained throughout the study. -UNIVERSITI TEKNOLOGI MARA